THE EFFECT OF COMPENSATION AND LEADERSHIP BEHAVIOR ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS A MEDIATING VARIABLE (Employee Study of PT PLN (Persero) UID Central Java & Special Region of Yogyakarta) - Flora Rosayanti Purba; Athoillah Athoillah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Human resources are essential for the success of an organization, especially in improving employee performance. However, employee performance is often influenced by several organizational factors such as compensation, leadership behavior, and job satisfaction. This study examines the influence of compensation and leadership behavior on employee performance with job satisfaction as a mediating variable. The research was conducted at PT PLN (Persero) UID Central Java and the Special Region of Yogyakarta. The method used in this study is a quantitative method with a sample of 116 employees. The sampling technique was selected through simple random sampling and analyzed using the Statistical Package for the Social Science version 29. These findings reveal that compensation and leadership behaviors significantly affect employee performance and job satisfaction. Job satisfaction also has a significant effect on employee performance and partly mediates the relationship between compensation and employee performance as well as between leadership behavior and employee performance. These results suggest that fair compensation and supportive leadership behaviors can improve job satisfaction, which further contributes to improved employee performance.